The relationship between self-awareness and self-control toward the understanding of basic sexual education - Hanifah, Zhafira Hana; Suprapto, Purwati Kuswarini; Diella, Dea (JURNAL BIOEDUKATIKA, 2024)
The goal of this study is to determine how the self-awareness and self-control of high school science majors relate to their understanding of basic sexual education through the study of the human reproductive system. The method used is mixed methods. The sample consisted of all 11th-grade science majors at one of the Tasikmalaya City high schools. In the sample, there were two classes. The sampling technique utilized was purposive sampling. Data were gathered by interviews with teachers and students, and questionnaires for self-awareness, self-control, and basic sexual education. Methodologies for descriptive qualitative data analysis also include precondition analysis and hypothesis testing, such as correlation tests with Spearman Rank and basic linear regression tests, in addition to drawing conclusions. Due to students' uncertainty regarding their ability to exercise self-control, the study's findings indicate that there is no correlation between self-control and understanding of basic sexual education. However, there is a correlation between self-awareness and understanding of basic sexual education with a low category, which is supported by student interviews in which up to 38.54% of students are confident in their responses. Additionally, there is a link between self-awareness and self-control and a low-category grasp of fundamental sexual education